Ifcee 2018 2018
DOI: 10.1061/9780784481585.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mesh Size, Number of Slices, and Number of Simulations in Probabilistic Analysis of Slopes Considering 2D Spatial Variability of Soil Properties

Abstract: The Random Limit Equilibrium Method (RLEM) is a relatively new method of probabilistic slope stability analysis which uses a combination of 2D random field theory, limit equilibrium methods, and Monte Carlo simulation. The Random Finite Element Method (RFEM) uses a combination of 2D random field theory, finite element method of analysis, strength reduction method, and Monte Carlo simulation. In this paper, the effects of mesh size, number of slices, and number of Monte Carlo simulations on computed probability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…The noncircular RLEM, introduced by Cami et al (2018), is a combination of the Cuckoo search method, the Surface Altering Optimization technique, and the LEM (Morgenstern-Price method) together with the random field theory. The Cuckoo search is a very fast and efficient global optimization method (metaheuristic approach), which is used for locating critical noncircular slip surfaces.…”
Section: Random Limit Equilibrium Methods (Rlem) Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The noncircular RLEM, introduced by Cami et al (2018), is a combination of the Cuckoo search method, the Surface Altering Optimization technique, and the LEM (Morgenstern-Price method) together with the random field theory. The Cuckoo search is a very fast and efficient global optimization method (metaheuristic approach), which is used for locating critical noncircular slip surfaces.…”
Section: Random Limit Equilibrium Methods (Rlem) Resultsmentioning
confidence: 99%
“…When used in conjunction with a noncircular search, this optimization method can be very effective and efficient at locating (searching out) slip surfaces with lower safety factors. Cami et al (2018) showed that noncircular RLEM was able to find the weakest failure path using local and global optimization techniques similar to the failure path using the RFEM approach. The run time for the noncircular RLEM was shown to be at least 40% less than running the same example using the RFEM method with the same output.…”
Section: Random Limit Equilibrium Methods (Rlem) Resultsmentioning
confidence: 99%
See 3 more Smart Citations